Difficulties in Emotion Regulation Predict Depressive Symptom Trajectory From Early to Middle Adolescence - Gonçalves, Stefanie F. (Child Psychiatry Hum Dev, 2019)
Major depressive disorder begins to increase in early adolescence and is associated with significant impairment (e.g., suicidality). Difficulties in emotion regulation (ER) have been associated with depressive symptoms; however, little research has examined this relation over time beginning in early adolescence. Starting when they were 11-14 years old, 246 adolescents (n(boys) = 126; n(white) = 158) completed self-report questionnaires on their ER at Time 1 and depressive symptoms every year for 2 years. Results revealed that overall difficulties in ER (and limited access to ER strategies) at Time 1 predicted depressive symptoms both cross-sectionally and longitudinally. Gender moderated this relation cross-sectionally, such that higher overall ER difficulties at Time 1 was more strongly associated with higher depressive symptoms for girls than for boys. These findings suggest that depression prevention efforts should promote adaptive ER in early adolescence, particularly for girls, in order to prevent the increases in depressive symptoms seen into middle adolescence.